Fluktuasi Kondisi Megabentos di Perairan Ternate, Maluku Utara - Ucu Yanu Arbi; Agustinus Harahap; Hendriks Alexander William Cappenberg (Jurnal Kelautan Tropis, 2020)
The coral reef was a habitat for several groups of biota that live in this ecosystem. Some species or group species of benthic fauna are known to be ecologically important and others are economically important so that they can be used as indicators to assess reef health. Research on megabenthic fauna in Ternate and its surrounding waters, North Maluku, was carried out in 2012, 2015, 2016, 2017 and 2018 at fourteen permanent stations. The purpose of this study was to determine the fluctuations in several megabenthic faunae temporarily. Data were collected using the modified Belt Transect Method, namely Benthos Belt Transek method. Eight species or groups of megabenthic fauna in the coral reef have been observed. The highest distribution and abundance of megabenthic fauna was coral polyps eating-snail of Drupella spp. The species wealth index decreased from 2012 to 2017 (1.17 to 1.05) but experienced an increase in 2018 (to 1.29). The relatively high dominance found in the megabenthic fauna community was observed in 2015, 2016 and 2017, while in 2012 and 2018 it had relatively low dominance. The megabenthic fauna community observed in 2012 and 2018 has relatively high diversity, whereas in 2015, 2016 and 2017, the diversity is relatively low. The megabenthic fauna community observed in 2012 and 2018 has spread evenly, while in 2015, 2016 and 2017, the relative prevalence of fauna is relatively uneven.  Terumbu karang merupakan habitat bagi beberapa kelompok biota yang hidup di dalamnya. Beberapa spesies atau kelompok spesies bentos diketahui bernilai ekologis pentingdan yang lainnya bernilai ekonomis penting sehingga dapat dijadikan sebagai indikator untuk menilai kesehatan terumbu. Penelitian fauna megabentos di perairan Ternate dan sekitarnya, Maluku Utara dilakukan pada tahun 2012, 2015, 2016, 2017 dan 2018 pada empat belas stasiun permanen. Tujuan penelitian ini adalah untuk mengetahui fluktuasi beberapa indeks ekologi megabentos dari tahun ke tahun. Pengambilan data menggunakan metode Benthos Belt Transect yang dimodifikasi dari Belt Transect Method. Sebanyak delapan kelompok jenis atau kelompok jenis megabentos pada perairan terumbu karang telah diamati. Sebaran dan kelimpahan megabentos tertinggi adalah siput pemakan polip karang Drupella spp. Indeks kekayaan spesies mengalami penurunan tahun 2012 hingga 2017 (1,17 menjadi 1,05), namun mengalami peningkatan pada tahun 2018 (menjadi 1,29). Dominansi yang relatif tinggi dijumpai pada komunitas megabentos yang teramati pada tahun 2015, 2016 dan 2017, sedangkan pada tahun 2012 dan 2018 memiliki dominansi yang relatif rendah. Komunitas megabentos yang teramati pada tahun 2012 dan 2018 memiliki keanekaragaman yang relatif tinggi, sedangkan pada tahun 2015, 2016 dan 2017 berkeanekaragaman relatif rendah. Komunitas megabentos yang teramati pada tahun 2012 dan 2018 memiliki kemerataan fauna yang relatif merata, sedangkan pada tahun 2015, 2016 dan 2017 memiliki kemerataan fauna yang relatif tidak merata.